2018
DOI: 10.1021/acs.jpcb.8b01530
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Plasticity in Tyrosine Kinase Inhibitor–Kinase Interactions Revealed with Fluorescence Spectroscopy and Theoretical Calculations

Abstract: To understand drug-protein dynamics, it is necessary to account for drug molecular flexibility and binding site plasticity. Herein, we exploit fluorescence from a tyrosine kinase inhibitor, AG1478, as a reporter of its conformation and binding site environment when complexed with its cognate kinase. Water-soluble kinases, aminoglycoside phosphotransferase APH(3')-Ia and mitogen-activated protein kinase 14 (MAPK14), were chosen for this study. On the basis of our prior work, the AG1478 conformation (planar or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…There are three major challenges in drug development summarised by Habgood et al 79 That is, (a) development of a good method to generate ensembles of a molecule's bioactive conformation; (b) rational analysis and modification of a pre-established bioactive conformation; and (c) approximation of real solution phase conformational ensembles in tandem with spectroscopic data such as IR, NMR and UV-Vis spectra. Further CMS studies of anilinoquinazoline TKIs with high potency (PD150335) 80 reveal that optically reportable conformation of the TKI is often more potent than the planar global minimum structure of the TKI. It seems that a correlation with flexibility and potency of a TKI exists, as flexible TKI conformers are able to fit and dock in the TK domain of EGFR.…”
Section: Photoelectron Spectroscopy and Electron Momentum Spectroscopymentioning
confidence: 99%
“…There are three major challenges in drug development summarised by Habgood et al 79 That is, (a) development of a good method to generate ensembles of a molecule's bioactive conformation; (b) rational analysis and modification of a pre-established bioactive conformation; and (c) approximation of real solution phase conformational ensembles in tandem with spectroscopic data such as IR, NMR and UV-Vis spectra. Further CMS studies of anilinoquinazoline TKIs with high potency (PD150335) 80 reveal that optically reportable conformation of the TKI is often more potent than the planar global minimum structure of the TKI. It seems that a correlation with flexibility and potency of a TKI exists, as flexible TKI conformers are able to fit and dock in the TK domain of EGFR.…”
Section: Photoelectron Spectroscopy and Electron Momentum Spectroscopymentioning
confidence: 99%
“…This approach is usually a good approximation for absorption (e.g. UV-vis) calculations [4,16,[33][34][35]. The GS properties include geometry, dipole moment, and electronic transitions (absorption) [36].…”
Section: The Top Seven Dft Functionals In Ground and First Essmentioning
confidence: 99%
“…The plasticity of structural elements of the ATP-binding site is critical for determining the inhibitor conformation and binding mode. For instance, Khattab et al [ 63 ] showed that the binding interaction of AG1478 with either a kinase important for bacterial drug resistance (APH(3′)-Ia) or a kinase important for pancreatic cancer (MAPK14) can result in a discrete change in AG1478 conformation on a rugged matrix of protein backbone. In this study the authors inferred conformational heterogeneity of the drug AG1478 from excitation spectra, polarity of the AG1478 binding pocket from the emission spectrum and restricted molecular dynamics in the AG1478–kinase complex from excitation-dependent emission spectra.…”
Section: Fluorescence Tyrosine-kinase Inhibitors and Beyondmentioning
confidence: 99%